Primary gastric lymphoma to T cells, not associated with HTLV1, with initial presentation of pathological fracture. Case report - Riveros Anglas, Marisa Estelita (2023)
Adult T-cell lymphoma (ATLL) is an aggressive neoplasm of T-lymphocytes, usually associated with human T-lymphotropic virus type 1 (HTLV-1). Variegated clinical presentation. Primary gastric lymphomas most frequently have type B non-Hodgkin lymphoma (NH) as an etiology, and a minimal percentage is due to T lymphocytes. Literature on primary gastric lymphomas due to HTLV1 Negative T cells that metastasize to bone is scarce. The case of a 41-year-old adult who was admitted for a pathological fracture is presented. At 15 days he presented diarrhea, abdominal distension. An upper endoscopy finds: "Ulcerated gastric lesions, neoproliferative appearance." Biopsy reported: Non-Hodgkin lymphoma to T lymphocyte. HTLV1: negative. He had 3 sessions of chemotherapy with CHOEP scheme. There was a favorable response, at first. Unfortunately DID NOT RETURN. He returned 2 months later in poor general condition. He presented complications, multi-organ failure, resulting in his death.